Influência da hipercolesterolemia sobre células-tronco mesenquimais da medula óssea de camundongos apoE knockout - Zanardo, Tadeu Ériton Caliman (2016)
Due to its characteristics and properties, mesenchymal stem cells have often been used in the treatment of diseases that affect a large part of the population and which entail high costs for the health system. However, to date, little is known about the functionality of mesenchymal stem cells derived from bone marrow of diseased individuals, for use in cell therapy. Thus, in the present study, we evaluated the influence of hypercholesterolemia on mesenchymal stem cells derived from bone marrow of apoE knockout mice. We evaluated the blood cholesterol and plasma oxidative stress and the production of reactive oxygen species, the percentage of apoptosis and senescence and possible morphological changes in mesenchymal stem cells derived from bone marrow of apoE-/- mice (hypercholesterolemic) and C57 mice (normocholesterolemic), at 2 months of age. It was observed that hypercholesterolemia, which develop spontaneously in apoE -/- mice promotes increased plasma oxidative stress (apoE -/- :29,83 ± 3,58 µmol/mg vs. C57: 11,20 ± 1,89 µmol/mg, p< 0,001, Student t test), as well as increased production of O2-• (1.5 fold, p <0.01, Student t test), H2O2 (1.4 fold, p <0.01, Student t test) and NO (1.3-fold, p <0.05, Student t test) in mesenchymal stem cells from bone marrow. Consequently, there was an increase in the percentage of senescent (apoE-/- : 4,1 ± 0,53% vs. C57: 0,7 ± 0,12%, p< 0,001, Student t test) and apoptotic cells (apoE-/- : 7,48 ± 0,32% vs. C57: 2,31 ± 0,15%, p< 0,0001, Student t test) and increase in size (apoE-/- : 30529 ± 664,5 a.u. vs. C57: 27429 ± 589,8 a.u. p< 0,01, Student t test), cell area (apoE-/- : 6142 ± 603,6 µm2 vs. C57: 3682 ± 267,7 µm2 , p<0,001, Student t test) and nuclear area (apoE-/- : 127,6 ± 8,31 µm2 vs. C57: 106 ± 4,69 µm2 , p<0,05, Student t test), in addition to morphological changes in culture and these cells at the mitochondrial level. Thus, hypercholesterolemia affects the functionality of mesenchymal stem cells from bone marrow, which may affect the effectiveness of using these cells to treat, cure or prevention of diseases.